SEMIGROUP-LIKE PROPERTY OF MITTAG-LEFFLER FUNCTION - Bambang Hendriya Guswanto (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2016)
In this article, we discuss the semigroup-like property of Mittag-Leffler function which is used to solve the initial value problem of an ordinary differential equation involving Caputo fractional derivative.